Effects of Maternal Deprivation on Anxiety, Depression, and Empathy in Male and Female Offspring of Wistar Rats in the Face of Novel Objects: - Khalifeh, Solmaz; Khodagholi, Fariba; Moghtadaei, Mehrad; Behvarmanesh, Ali; Kheradmand, Afshin; Ghazvini, Hamed (Galen Medical Journal, 2019)
Background: Early life stress (ELS) models such as maternal deprivation (MD) are used to in¬vestigate behavioral changes in rodents under stressful situations. MD is a situation in which rat pups are separated from the dam; MD has different paradigms. The purpose of this research is to evaluate the effects of maternal deprivation on anxiety, depression, and empathy in adult Wistar rats. Materials and Methods: MD was applied to pups as per specifically designed protocol to compare rats of the control group with maternal deprivation rats and also the group, which faced novel objects. Each group consisted of eight rats. In this study, separation started from postnatal day (PND) 14 for various periods up to PND 60. EPM test was undertaken to measure anxiety; moreover, FST was used to indicate levels of depression. Also, changes in the empathy ratio were also demonstrated. One-way analysis of variance (ANOVA), Tukey’s post hoc analysis, and t-test were applied to analyze the results. Results: MD-treated rats showed a significant decrease in anxiety and empathy indexes compared with those in the control group (P<0.05). However, MD significantly increased depression in both male and female rats (P<0.05). Final¬ly, exposure to novel objects decreased depression but did not have any effect on anxiety and empathy levels in MD rats (P<0.05). Conclusion: ELS may lead to various states of mood and behavior in adulthood. According to the findings of this study, depression increases due to MD, though both anxiety and empathy decrease in both male and female Wistar rats. Moreover, ex¬posure to novel objects decreases depression, while anxiety and empathy do not change signifi¬cantly with exposure to novel objects. [GMJ.2019;8:e1093]